GAMBARAN PERSEPSI MASYARAKAT TERHADAP VAKSIN COVID-19 DI KELURAHAN KALIBENDA KABUPATEN BANJARNEGARA - Kusumo, Kelvin Angling; Handayani, Rahmaya Nova; Burhan, Asmat (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p13, 2023)
Coronavirus 2019 (Covid-19) is the virus responsible for the pandemic in all countries of the world. This disease is caused by the SARS-CoV-2 virus. The Covid-19 fraction of confirmed cases and the death rate is around 2,67 percent. Giving vaccines to the community is one of the prevention methods used to control transmission. This research is quantitative research using descriptive methodology and cross-sectional design. The research was conducted in November 2021 to July 2022 in depth with 147 community members in the Kalibenda Village, Sigaluh District, Banjarnegara Regency using purposive sampling technique and offline questionnaire distribution. Public opinion on Covid-19 immunization is good, which is determined by the achievement of vaccination objectives, vaccine safety, vaccine efficacy, and religious beliefs about vaccination, according to the research findings. This view affects public acceptance of the Covid-19 vaccine. This method of vaccination was rejected because of the bad attitude of society. Based on scientific findings, education can be directed at all categories of respondents who are not ready to get the Covid-19 immunization. Through this educational campaign, it is hoped that the public will be provided with sufficient knowledge and research-based evidence to limit the spread of false information about the Covid-19 vaccination.